Political, Economic, and Environmental Implications for Policies of the COVID-19 Pandemic: Global Perspective - Lucca, Anggie Parawitha; priambodo, bayu; Perbawani, Firsty Chintya Laksmi (Jurnal Hubungan Internasional, 2023)
The coronavirus pandemic has brought the world into an era that was previously unimaginable. Many life arrangements have changed a lot. This study looks at how the political, economic and environmental arrangements have changed due to COVID-19. The method in this study uses qualitative where the data search uses a library study. The results of the study show that from a political perspective, the pandemic poses a challenge to democracy as a value system and political system. The experience of an authoritarian country facing a pandemic, such as China, is promoted as the most ideal model for dealing with crises. From an economic perspective, as the business world was hit, the trend emerged was the rise of the state as the actor who played the most role in the economy. This can be seen from various policies such as nationalizing important sectors, saving corporations, and providing assistance to affected people.